Evaluation of Information Security at the Radin Inten II Lampung Meteorological Station Using the KAMI Index - Ardiansyah, Ardiansyah; Irianto, Suhendro Yusuf; Hasibuan, M. Said (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Information security is a way to protect information assets from various potential threats. BMKG is a Non-Departmental Government Institution (LPND) in Indonesia whose main duties involve carrying out government duties in the fields of meteorology, climatology and geophysics. In connection with delivering information services appropriately and precisely to stakeholders, the Radin Inten II Lampung Meteorological Station needs to carry out an independent assessment in terms of security to evaluate the information system in each work unit, with the aim of understanding the level of readiness and maturity of information security. This research aims to measure the level of information security maturity at the Radin Inten II Lampung Meteorological Station. The analysis method used in this research is using the KAMI Index version 5.0 based on the ISO/IEC 27001:2022 standard. The research results indicate that the implementation of the ISO 27001:2022 standard in the information system of the Radin Inten II Lampung Meteorological Station is considered good. The total score obtained reached 591 based on analysis and questionnaires using the KAMI Index. With this score, the Radin Inten II Lampung Meteorological Station information system is categorized at level III, which indicates that some improvements are still needed.